O controle judicial das decisões proferidas pelo Carf favoráveis ao contribuinte - Xavier, Bianca Ramos (2016)
Analyze the ruling effects on the phenomenon of tax incidence will be the purpose of this doctoral dissertation. The goal is to investigate if the Judiciary can deconstitute it in cases of the favorable decision to the taxpayer's interests. In case of the positive answer to establish the deconstitution boundaries of the Carf's decision. This research will be very important because the judicial review main will result in the weakening of tax administrative litigation and the glut of tax litigations at the judicial level. The analysis will be carried out taking into account the role of the tax assessment on the tax incidence, the structure of the tax administrative litigation, the administrative judicial review of doctrine of administrative acts and, finally, the possibility of judicial review of 64 Carf's lawsuits